The Effectiveness of Hybrid Learning in English Pronunciation Pedagogy in the Nigerian ESL Context - Jacinta Benjamin-Ohwodede; Adekunle Mamudu; Simeon Nyemike Awunor (JELITA, 2024)
This paper is a study on the effectiveness of hybrid learning; a blend of traditional and technology-based training, vis-à-vis the second language (L2) learner of English pronunciation. Specifically, our motivation is centred on the functionality of combining the habitual classroom teaching style with the Telegram app (a mobile-based technological tool) for studies relating to speech production and perception. The methodical procedure and design for this study is both quantitative and descriptive; employing the use of a multiple-choice questionnaire in data collection from 401 Nigerian undergraduate and postgraduate students in the University of Benin, Nigeria, to ascertain the effectiveness of digital designs and stratagems. Pie charts are employed to display multiple divisions of the study's data comparison. This study emphasizes the Online-Driver Blended Learning Model; such a pedagogical approach exposes the L2 learner to a more involved and effective way of understanding how to avoid imposing an unfamiliar accent upon the target language. Consequently, we see a merger of online practical exercises and exposure to uploaded multimodal texts and native speakers' spoken data (audio-visual recordings/voice notes) with scheduled direct classroom interludes. Findings confirm that exploiting such a hybrid model enhances students' cognitive abilities and retentive capacity regarding English pronunciation. Such digital audio-visual tools are paramount phonetic strategies for learning how to avoid unacceptable phonetic alterations. Thus, we see the effectiveness of integrating the Telegram app into the traditional brick-and-mortar educational method in handling problems associated with speech sound production and second-language phonological interference.